A furnace and environmental cell for the in situ investigation of molten salt electrolysis using high-energy X-ray diffraction - Styles, M.; Rowles, Matthew; Madsen, I.; McGregor, K.; Urban, A.; Snook, G.; Scarlett, N.; Riley, D. (Blackwell Publishing, 2012)
This paper describes the design, construction and implementation of a relatively large controlled-atmosphere cell and furnace arrangement. The purpose of this equipment is to facilitate the in situ characterization of materials used in molten salt electrowinning cells, using high-energy X-ray scattering techniques such as synchrotron-based energy-dispersive X-ray diffraction. The applicability of this equipment is demonstrated by quantitative measurements of the phase composition of a model inert anode material, which were taken during an in situ study of an operational Fray-Farthing-Chen Cambridge electrowinning cell, featuring molten CaCl(2) as the electrolyte. The feasibility of adapting the cell design to investigate materials in other high-temperature environments is also discussed.